Konstruksi Heterotopia Pada Platform OTT Netflix - Hendra, Wahyu Oktana (Sekolah Pascasarjana Institut Kesenian Jakarta, 2020)
The presence of the Netflix OTT platform in the film and television world has caused a shift in the film-watching ecosystem from cinemas to new alternative spaces for viewing. This paper will discuss the heterotopia construction that occurs on the Netflix OTT platform. The construction of heterotopia in this article will be discussed using the heterotopia approach initiated by Michel Foucault using qualitative descriptive analysis methods to analyze and disclose data as information media using field survey techniques and literature review. The results of the study show that the Netflix OTT platform space fulfills most of the heterotopia concept space proposed by Foucault. In addition, the various principles of heterotopia space that exist on the Netflix platform are also in line with Foucault’s views. Analysis of aspects of crisis and deviation, function, juxtaposition, time, place, and society shows that there is a relationship and affinity between real space and unreal space that complement each other and cannot be separated from one another on the Netflix OTT platform.Hadirnya platform OTT Netflix di dunia film dan televisi menyebabkan terjadinya pergeseran ekosistem menonton film dari bioskop ke alternatif ruang baru tempat menonton. Tulisan ini akan membahas konstruksi heterotopia yang terjadi pada platform OTT Netflix. Konstruksi heterotopia dalam artikel ini akan dibahas dengan pendekatan heterotopia yang digagas oleh Michel Foucault menggunakan metode analisis deskriptif kualitatif untuk menganalisis dan mengungkapkan data sebagai media informasi dengan teknik survei lapangan dan tinjauan pustaka. Hasil penelitian memperlihatkan bahwa ruang platform OTT Netflix memenuhi sebagian besar konsep ruang heterotopia yang digagas Foucault. Di samping itu, berbagai prinsip ruang heterotopia yang ada di platform Netflix juga selaras dengan pandangan Foucault. Analisis aspek crisis and deviation, function, juxtaposition, time, place, dan society memperlihatkan adanya hubungan dan pertalian antara ruang nyata dan ruang tidak nyata yang saling mengisi dan tidak dapat dipisahkan satu dengan lainnya yang terdapat di platform OTT Netflix.